Hybrid Learning Model in Islamic Education: Challenges and Opportunities in the Digital Era - Akhmad Khoiri; Munawaroh Munawaroh; Ahmad Hadi Setiawan; M Rifki Mukhtar; Dewangga Ramadhan (IQRO: Journal of Islamic Education, 2026)
The development of digital technology encourages Islamic educational institutions to develop adaptive learning models without neglecting Islamic values. This study aims to analyze the opportunities and challenges of the Hybrid Learning model in Islamic Education and formulate a conceptual model that integrates pedagogy, digital technology, and the internalization of Islamic values. The study used a descriptive qualitative approach, located at IAI Darul Fattah Lampung. Data were collected through observation, interviews, and questionnaires. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results indicate that Hybrid Learning offers opportunities to increase learning flexibility, expand access to learning resources, develop learning independence, and strengthen students' 21st-century competencies and digital literacy. However, its implementation requires systematic pedagogical design, adequate technological support, and the integration of Islamic values ​​into every learning activity. The novelty of this research lies in the development of a Hybrid Learning conceptual model that combines three main dimensions: pedagogy, digital technology, and the internalization of Islamic values. This research can serve as an alternative strategy for transforming Islamic Education in the digital era.